Modificação do método de obtenção do corte axial da maxila para avaliação tomográfica da maturação da sutura palatina mediana - Miguita, Luiz Fernando Tadano (2018)
Introduction: The aim of this study was to elaborate a modification in the method to obtain an axial cut of the maxilla, which accompanies the palatine anatomy for the evaluation fo the maturation stage of the median palatine suture (MPS) and to compare it with the original method. Methods: The sample consisted of 84 conical beam computed tomography (CBCT) examinations of 40 boys and 44 girls, aged 11 to 15 years. The files were exported to the Nemotec Dental Studio program, by means of which the axial cuts of the maxilla were obtained, traced in order to accompany the palatine anatomy, keeping the buccal and nasal cortical bones centralized and equidistant. Two previously calibrated evaluators classified the axial images of the MPS in maturational stages according to their morphology. The kappa values for intra and inter-examiner agreement were 0.88 and 0.69 respectively. The significance level adopted for the statistical tests was 0.05%. Results: The modification of the method was able to evaluate the “status” of MPS maturation and demonstrated more advanced stages of this maturation when compared to the original method. Conclusions: The method allowed classifying the MPS stage, likewise the original method, with the advantage of obeying the concept of evaluation of this process in the midline of the palate, when the palate was curved and/or thick.